Source: Submitted by Jason Telgren, citing Sarah Everding. I'd be interested in similar puzzles others might have.
Let AB=a,CG=b, IC=x and JC=y ABE and ICE are similar==>x=ab/(a+b) DGF and DCJ are similar==>y=ab/(a+b) Aria(ICE)=abb/2(a+b) and Aria(DEJ)=(a/2)(b-ab/(a+b))=abb/2(a+b)==> Aria(ICE)=Aria(DEJ)==>Aria(ICE)-Aria(HJE)=Aria(DEJ)-Aria(HJE)==> Aria(HICJ)=Aria(DHE)Phillipe Fondanaiche sent:
Let a=side of ABCD and b=side of EFGC. As ADI and CEI are similar triangles,CI/b = (a-CI)/a => CI = ab/(a+b) and DI = a^2/(a+b) As CDJ and EFG are similar triangles,CJ/a =(b-CJ)/b => CJ = ab/(a+b) = CI Area(HJCI) + area(DIH) = area(DCJ) = DC x CJ /2 = a^2xb/2(a+b) Area(DHE) + area(DIH) = area(DEI) = DI x CE /2 = a^2xb/2(a+b) So, area (HJCI) = area(DHE)My (Ken's) solution is a little more complicated:
Add a point X at the intersection of AD and EF. Now AE divides rectangle AXEB in half. And DF divides rectangle DXFG in half. So, (all combinations of letters describe areas): DFG - DXF + ABE - AXE = 0 Expanding (areas EJH and DIH have cancelled out.): (ABCI - ADI) + (CJFG - EJF) -2DXE + 2(HICJ - DHE) = 0 Let EF=a, AD=b. Then: ADI = (b/2)(b/a+b)(b) = (b^3)/[2(a+b)] ABCI = (b^2) - ADI EJF = (a^3)/[2(a+b)] CJFG = (a^2) = EJF DXE = ab/2 Substituting: (a^2 + b^2) - (a^3 + b^3)/(a+b) - ab + 2(HICJ - DHE) = 0 (a^2 + b^2)(a+b) - (a^3 + b^3) - ab(a+b) + 2(a+b)(HICJ - DHE) = 0 a^3 + ab^2 + ba^2 + b^3 - a^3 - b^3 - ba^2 - ab^2 + 2(a+b)(HICJ - DHE) = 0 0 + 2(a+b)(HICJ - DHE) = 0 So DHE = HICJ.